Business Impacts of CrossFit Affiliates and the 60+ Age Group - Craw, Michael; Elliot, Jeremy; Woodroffe, Jessica (Journal of Sports Research, 2021)
The purpose of this study was to investigate CrossFit Affiliate owner/ operators’ insights of their fitness business as it applies to the fitness experience of people aged 60+. The objective of this study was to reveal how CrossFit may encourage older adult populations into fitness levels and improved health. The aim of the study was to investigate a unique fitness-business model to reveal fitness experience success for future wellness delivery in aging populations. A qualitative study of purposeful sampling explored the business-related experiences of affiliate owner/ operators that provide regular group exercise to 60+ age population membership. Participants from CrossFit Affiliates in Southeastern Australia (9) and Southeastern United States (3) each answered a fifteen (15) question survey. Given the lens of the study, data was analyzed using a systematic search for information to identify business themes that encourage fitness in aging populations that included the ESOMAR/ GRBN guidelines (2015), Schein (2010), and Ryan, Coughlan, and Cronin (2009) process for conducting face-to-face interviews. Braun & Clarke, Bree & Gallagher, and Maguire & Delahunt’s recommendations identified for themes. A liturgical-like fitness experience including, capturing personal transformation/ social transformation/ accountability/ creativity/ purposefulness, comradery and community is beneficial to encouraging a supportive box culture that encourages aging populations to participate in CrossFit. Information from this study be used by private public sector partnerships to make a meaningful contribution to the health and wellbeing of aging populations with view to better healthcare outcomes for an aging society.